2012
DOI: 10.1155/2012/205313
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Identification of Potential Immunodominant Epitopes in Glycoproteins B, C, E, G, and I of Herpes Simplex Virus Type 2

Abstract: Twenty B candidate epitopes of glycoproteins B (gB2), C (gC2), E (gE2), G (gG2), and I (gI2) of herpes simplex virus type 2 (HSV-2) were predicted using DNAstar, Biosun, and Antheprot methods combined with the polynomial method. Subsequently, the biological functions of the peptides were tested via experimentsin vitro. Among the 20 epitope peptides, 17 could react with the antisera to the corresponding parent proteins in the EIA tests. In particular, five peptides, namely, gB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This is the first time that these epitopes have been identified by serology with clinical samples and thus represent novel candidates for further selection (see below). However, parts of the last sequence gE2 451–545 have been previously predicted to show antigenicity . In the case of gG the glycoproteins gG1 and gG2 differ significantly in terms of size and sequence, but scattered reactivity to both gG1 and gG2 was found on sequences with homology (Figure i,j).…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is the first time that these epitopes have been identified by serology with clinical samples and thus represent novel candidates for further selection (see below). However, parts of the last sequence gE2 451–545 have been previously predicted to show antigenicity . In the case of gG the glycoproteins gG1 and gG2 differ significantly in terms of size and sequence, but scattered reactivity to both gG1 and gG2 was found on sequences with homology (Figure i,j).…”
Section: Results and Discussionmentioning
confidence: 90%
“…For comparison, data in Figure d from gG2 were extracted from Clo et al No significant serum reactivity was found on gH peptides (Figure k,l). Surprisingly, a large difference was found between gI1 and gI2 (Figure m,n) with intense serum responses on gI2 peptides, despite a significant sequence homology.…”
Section: Results and Discussionmentioning
confidence: 95%
“…Epitope-based vaccines have for long stood out as promising vaccine candidates against diverse pathogens (Christy et al 2012;Hurtgen et al 2012;Pan et al 2012;Kunthalert et al 2013;Rojas-Caraballo et al 2014) and have forayed their way in human clinical trials as well (Iinuma et al 2014). Other than helping to focus on and thereby narrowing down the specificity of immune response, they also leave room for chimera generation including multiple epitopes from same as well as different and slightly more immunogenic antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Many neutralizing antibodies against HCV gpE2 gene are reported; however these antibodies differ in their mechanism of neutralization and are mostly homologus in action ( 17 ). Recent studies have proved that predicted epitopes by different online tools shows immunogenicity when experimentally checked in herpes simplex virus, influenza A virus , and Vibriomimicus ( 30 , 31 ). The human antibodies raised against HCV gpE2 epitopes do not offer protection against multiple viral infections; the preseason may be related to either genetic variations among viral strains particularly within the hyper variable region-1 (HVR-1), low titers of anti-gpE2 antibodies, or interference of non-neutralizing antibodies with the function of neutralizing antibodies ( 32 ).…”
Section: Discussionmentioning
confidence: 99%